Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To rewrite the equation [tex]\(4x^4 - 21x^2 + 20 = 0\)[/tex] as a quadratic equation, we can use a suitable substitution. Let's go through the steps to determine the appropriate substitution step-by-step.
1. Identify the target form: We need to transform the given equation into a standard quadratic form, which is generally [tex]\(au^2 + bu + c = 0\)[/tex].
2. Analyze the equation: The given equation is [tex]\(4x^4 - 21x^2 + 20 = 0\)[/tex]. Notice the terms involve [tex]\(x^4\)[/tex] and [tex]\(x^2\)[/tex].
3. Choose a substitution: We want to transform the variable so that [tex]\(x^4\)[/tex] becomes a quadratic term and [tex]\(x^2\)[/tex] becomes a linear term.
- If we let [tex]\(u = x^2\)[/tex], then:
[tex]\[ x^4 = (x^2)^2 = u^2 \][/tex]
Thus, substituting [tex]\(u\)[/tex] into the equation, we get:
[tex]\[ 4(u^2) - 21u + 20 = 0 \][/tex]
This simplifies to:
[tex]\[ 4u^2 - 21u + 20 = 0 \][/tex]
This is a quadratic equation in terms of [tex]\(u\)[/tex].
- Consider other options:
- [tex]\(u = 2x^2\)[/tex]: This would make the substitution more complex and would not lead to a straightforward quadratic equation.
- [tex]\(u = x^4\)[/tex]: This does not simplify our goal, as [tex]\(u = x^4\)[/tex] would not eliminate the [tex]\(x^2\)[/tex] term properly.
- [tex]\(u = 4x^4\)[/tex]: Similar to [tex]\(u = x^4\)[/tex], it would not simplify the equation to the desired quadratic form.
4. Conclusion: The correct substitution that rewrites the given equation [tex]\(4x^4 - 21x^2 + 20 = 0\)[/tex] as a quadratic equation is [tex]\(u = x^2\)[/tex].
The correct choice is:
[tex]\[ \boxed{u = x^2} \][/tex]
1. Identify the target form: We need to transform the given equation into a standard quadratic form, which is generally [tex]\(au^2 + bu + c = 0\)[/tex].
2. Analyze the equation: The given equation is [tex]\(4x^4 - 21x^2 + 20 = 0\)[/tex]. Notice the terms involve [tex]\(x^4\)[/tex] and [tex]\(x^2\)[/tex].
3. Choose a substitution: We want to transform the variable so that [tex]\(x^4\)[/tex] becomes a quadratic term and [tex]\(x^2\)[/tex] becomes a linear term.
- If we let [tex]\(u = x^2\)[/tex], then:
[tex]\[ x^4 = (x^2)^2 = u^2 \][/tex]
Thus, substituting [tex]\(u\)[/tex] into the equation, we get:
[tex]\[ 4(u^2) - 21u + 20 = 0 \][/tex]
This simplifies to:
[tex]\[ 4u^2 - 21u + 20 = 0 \][/tex]
This is a quadratic equation in terms of [tex]\(u\)[/tex].
- Consider other options:
- [tex]\(u = 2x^2\)[/tex]: This would make the substitution more complex and would not lead to a straightforward quadratic equation.
- [tex]\(u = x^4\)[/tex]: This does not simplify our goal, as [tex]\(u = x^4\)[/tex] would not eliminate the [tex]\(x^2\)[/tex] term properly.
- [tex]\(u = 4x^4\)[/tex]: Similar to [tex]\(u = x^4\)[/tex], it would not simplify the equation to the desired quadratic form.
4. Conclusion: The correct substitution that rewrites the given equation [tex]\(4x^4 - 21x^2 + 20 = 0\)[/tex] as a quadratic equation is [tex]\(u = x^2\)[/tex].
The correct choice is:
[tex]\[ \boxed{u = x^2} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.